Faktor – Faktor yang Mempengaruhi Kualitas Pelayanan Publik di Kantor Pertanahan Kota Semarang - Riska Aidina Pristiria; Kismartini Kismartini; Ida Hayu Dwimawanti (PERSPEKTIF, 2022)
This study aims to determine the effect of organizational structure, employee capabilities and service facilities on service quality at the Land Office of Semarang City. The main data used is a questionnaire consisting of 27 question items, distributed to people who register and receive land services from Kantor Pertanahan Kota Semarang, either direct applicants or authorized recipients of 377 respondents. The data obtained were analyzed by multiple linear regression using the SPSSv16 software application. The results show that the quality of service at the Kantor Pertanahan Kota Semarang is currently in the good category (average 3.14), even so, there are still several things that need to be addressed related to guaranteeing the timeliness of service management and the accuracy of service costs. There is a significant influence between organizational structure factors, employee capabilities and service facilities on the quality of service both simultaneously at 63.1% and partially at 29.9%, 35.2% and 8.3% respectively. The most dominant factor in determining service quality in this study is the employee ability factor of 35.2%, followed by the organizational structure factor of 19.9% and the service facility factor of 8.3%.